2011
DOI: 10.1155/2011/848309
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Administration Modulates Cortical TLR4/NF-κB Signaling Pathway after Subarachnoid Hemorrhage in Male Rats

Abstract: Our previous study concerning brain trauma has shown that progesterone could regulate toll-like receptor 4 (TLR4) and nuclear factor-kappa B (NF-κB) signaling pathway in the brain, which also has been proved to play important roles in early brain injury (EBI) after subarachnoid hemorrhage (SAH). The aim of the current study was to investigate whether progesterone administration modulated TLR4/NF-κB pathway signaling pathway in the brain at the early stage of SAH. All SAH animals were subjected to injection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 35 publications
3
54
0
Order By: Relevance
“…One interesting hypothesis may be progesterone modulation of aquaporin 4 channels [45], which are known to be associated with edema formation after ICH [46]. Another possibility lies in progesterone's known modulation of the NFκB pathway through TLRs [42,47,48], as supported by the present findings. Understanding the ICH-specific mechanisms of progesterone's action would improve the likelihood of its successful translation as a therapeutic.…”
Section: Discussionsupporting
confidence: 73%
“…One interesting hypothesis may be progesterone modulation of aquaporin 4 channels [45], which are known to be associated with edema formation after ICH [46]. Another possibility lies in progesterone's known modulation of the NFκB pathway through TLRs [42,47,48], as supported by the present findings. Understanding the ICH-specific mechanisms of progesterone's action would improve the likelihood of its successful translation as a therapeutic.…”
Section: Discussionsupporting
confidence: 73%
“…Then we found that inhibition of TAK1 resulted in less NF-B activation and less neuronal apoptosis in vivo (15). NF-B has emerged as one of the most promising molecular targets in the prevention of EBI (6,26). NF-B resides in the inactive state in the cytoplasm as a heterotrimer consisting of p50, p65, and IB␣ subunits.…”
Section: Tak1 Inhibition Attenuates Early Brain Injury After Sahmentioning
confidence: 95%
“…In addition to MAPK signaling pathways, NF-B also plays a key role in the pathogenesis of early brain injury after SAH (6,26). To determine the effect of TAK1 inhibition on NF-B signaling in EBI in this study, we investigated the effect of OZ on IB, an inhibitor of NF-B.…”
Section: Effect Of Tak1 Inhibition On Sah-induced Nuclear Translocatimentioning
confidence: 99%
“…As another pivotal signaling pathway, NF-κB pathway has been deemed to play a dominating role in inflammation post-SAH, which could be activated due to excess ROS generation. Accumulating evidence demonstrated that many agents (recombinant osteopontin, urinary trypsin inhibitor, trehalose, progesterone, et al) alleviated inflammatory response after SAH, partially via inhibiting NF-κB inflammatory pathway [24][25][26][27]. NLRP3 inflammasome is another key component of inflammatory response.…”
Section: Introductionmentioning
confidence: 99%